Dampak Model Pembelajaran AGT Re-Con Terhadap Peningkatan Hasil Belajar dan Self Regulated Learning Siswa MTs - Sri Hartatik; Wachju Subchan; Joko Waluyo (Program Studi Magister Pendidikan IPA FKIP Universitas Jember Bekerjasama dengan Perkumpulan Pendidik IPA Indonesia (PPII), 2016)
Learning model of AGT Re-Con (Auditory, Guiding, Testing, Repetition and Conclussion) is combined between learning model of GIL (Guided Inquiry Learning) and AIR (Auditory Intelectually and Repetiiton). The purpose this research is one of to description of final learning and self regulated learning students with using learning model of AGT-Con. The aim of this research is for first grade student of MTs Negeri Arjasa in academic year 2015/2016 that helding research for three times meeting. The learning result to analyze using N-gain. Analysis with N-gain to get the first meeting 0,50, second meeting 0,51 and third meeting 0,75, meanwhile self regulated learning the high percentage student for indicator Organizing and Transforming.